Role of 2D material families in energy harvesting: an editorial overview - Raghavan, Prasanth; Ahn, Jou-Hyeon; Shelke, Manjusha (Journal of Materials Research, 2022)
The ever increasing proportion of an energy consuming society and the boost in industrialization accelerated the depletion of fossil fuel based energy sources at an alarming rate. This emphasizes the necessity of sustainable energy generation and storage to meet the daily energy demands. But, these alternative renewable energy sources like solar and wind power are intermittent and highly depend on weather, place and individuals. This creates the inevitability of suitable energy storage devices like batteries and supercapacitors. The interfacing of energy storing devices is required to maintain the supply chain equilibrium, power efficiency, regulate power fluctuations and reduce pollution. Besides, the boom in electric mobility and consumer electronics also require uninterrupted power supply. Hence, in the upcoming years the energy storing devices play a vital role in addressing the energy crisis. Innovations in new materials and technologies will be the core area of research and development in the coming future. 2D materials like graphene,transition metal carbides and nitrides (MXenes), transition metal borides (MBenes) and so on are the new class of materials among them MXenes are getting more attention in energy storage owing to its exceptional properties.